Valourization of using efficiency of filtration drying for alcohol distillery stillage - O.S. Ivashchuk; V.M. Atamanyuk; R.A. Chyzhovych (Case Studies in Chemical and Environmental Engineering, 2024)
The article presents the results of the calculation of specific energy consumption for the filtration drying process of corn alcohol distillery stillage. It was determined that the optimal total energy consumption for the evaporation of 1 kg of moisture during the filtration drying of corn alcohol distillery stillage from the initial moisture content of the material ω1 = 72.78 % wt. to the final value ω2 = 14 % wt. is 9468.96 kJ/kg H2O or 2.63 kW h/kg H2O for the following process parameters: the height of the layer of dried material H = 120 mm, the thermal agent temperature T = 90 °C, the thermal agent velocity v0 = 1.76 m/sec. Based on the selected optimal parameters of the filtration drying process of corn alcohol distillery stillage at the experimental installation, an evaluation calculation of the efficiency of filtration drying in industrial conditions was made. The total amount of energy required to dry ⁓ 1000 kg of corn alcohol distillery stillage in the filtration drying installation is approximately 1923.91 kW h. The total energy consumption for the removal of 1 kg of moisture during the test material drying at an industrial filtration drying installation is approximately 2.64 kW h/kg H2O. To compare the effectiveness of the filtration method of drying for corn alcohol distillery stillage, it was calculated for drying under a similar technical task in a rotary dryer. During the drying of 1000 kg of corn alcohol distillery stillage, a total of approximately 2146.91 kW h of energy is required, and the total energy consumption for removing 1 kg of moisture during the corn alcohol distillery stillage drying in a rotary dryer is approximately 3.13 kW h/kg H2O. It was calculated that the use of the filtration drying method makes it possible to reduce the specific energy consumption for removing 1 kg of moisture by 15.65 % with the required amount of thermal agent compared to drying in a rotary dryer. The use of filtration drying in industry would have a higher economic effect, given the higher heat losses in a rotary dryer to the environment and the need for energy-intensive auxiliary equipment for rotary dryers.